Analysis of the heat transfer area distribution in a frosted plain fin-and-tube geometry. (March 2017) - Morales-Fuentes, A.; Chapa-Contreras, O.M.; Méndez-Díaz, S.; Belman-Flores, J.M.
Highlights: Thermohydraulic analysis of a domestic evaporator during frost formation is studied. The humid airflow is re-distributed among channels as frost layer develops. The geometry performance is dictated by fin spacing, length and flow distribution. A rapid frost development leads to restriction in pressure drop rather than thermal. Abstract: The development of frost is a phenomenon that deteriorates thermohydraulic performance on heat exchangers. In this study, several heat-transfer area distributions on a fin-and-tube geometry are proposed and their performances as frost develops are compared using simulation. The frost development at a specific location is determined using a segment analysis. In each segment, a semiempirical model to predict the frost growth based on air temperature, velocity, relative humidity and surface temperature is applied. The analysis considers airflow redistribution among channels, leading to changes in heat transfer and frosting rates with time. Results show that a geometry that allows even flow distribution along the operation time is less sensitive to thermohydraulic deterioration. An area distribution with larger fin spacing and fin length presents an advantage, particularly on the pressure drop, which allows longer operation time between defrost cycles.